Owen - Henkes, Kevin (New York : Greenwillow Books, 1993)
Owen's parents try to get him to give up his favorite blanket before he starts school, but when their efforts fail, they come up with a solution that makes everyone happy.
Sch Libr Jnl
Horn Book
Publ Weekly
3.0
Keywords: Blankets -- Fiction; Parent and child -- Fiction